Hubungan Antara Kecemasan Sosial dengan Perilaku Phubbing pada Dewasa Awal - Asla Hanifah Putri; Yulia Fitriani; Fathana Gina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study aims to determine the relationship between social anxiety and phubbing behavior in early adulthood. Phubbing refers to the act of ignoring a conversation partner during face-to-face interactions due to greater attention being directed toward a smartphone. One factor that is believed to be associated with this behavior is social anxiety, which is characterized by feelings of fear, worry, and discomfort in social situations. Individuals experiencing higher levels of social anxiety may prefer engaging with their smartphones rather than participating in direct interpersonal interactions.This study employed a quantitative approach with a correlational research design. The participants consisted of 144 young adults aged 18–25 years who were unmarried and resided in Bekasi Regency. Participants were selected using a purposive sampling technique. Data were collected using the Generic Scale of Phubbing (GSP) and a social anxiety scale. The data were analyzed using Spearman’s rho correlation test to examine the relationship between the variables.The findings revealed a significant positive relationship between social anxiety and phubbing behavior among young adults (r = 0.765; p < 0.001). The correlation coefficient indicates a strong relationship, suggesting that individuals with higher levels of social anxiety are more likely to engage in phubbing behavior. Therefore, the research hypothesis was accepted. The results also highlight the role of social anxiety as a psychological factor associated with phubbing behavior in early adulthood. Based on these findings, young adults are encouraged to develop greater awareness of their social anxiety and adopt adaptive coping strategies to reduce the tendency to engage in phubbing. Future studies are recommended to involve more diverse participants and explore additional factors that may influence phubbing behavior